THE ROLE OF DEMOCRATIC VALUES AND PRINCIPLES IN INCREASING THE RESPONSIBILITY OF LOCAL GOVERNMENT OFFICERS - Nusratjon Tursunov (International Scientific and Current Research Conferences, 2023)
This article discusses the role of democratic values and principles in increasing the responsibility of local government officers.